The Functions of “epithet” in Haft Peykar by Nizami - Azadeh Sotodeh; Masoud Pakdel; Mansooreh Tadayooni; Sima Mansoori (مطالعات زبانی و بلاغی)
In English rhetoric, the epithet is when they use the characteristics of something or someone with its name or instead of its name. This definition is identical to "irony of the adjective" or "irony of the noun" in the Persian rhetoric. Studies show that some research has been done in this area and they have introduced epithet with greater development and have failed to provide brilliant examples of the use of this artistic tool. Epithet can be an artistic use of the adjective which makes the word more "literary". However, in the English rhetoric, epithet is more commonly found in epic texts, but research shows that in texts that value "rhetoric" and, more generally, "poetry", epithet emerges on a broader level. In the present study, Masnavi by Nizami (Haft Peykar), which is full of epic elements, is investigated and analyzed from the point of view of applying epithet and this question has been answered: What are the functions of epithet in “Haft Peykar” by Nizami? The results show that Nizami has made the most of epithet to create all sorts of ambiguities, paradoxes, descriptions, characterization and some other exquisite literary arrays. It seems that to find a variety of rhetorical arts, consideration of epithet in his works, especially “Haft Peykar”, is essential.